No laughing white matter: Reduced integrity of the cortical cholinergic pathways in Parkinson's disease-related cognitive impairment - Crockett, Rachel A.; Wilkins, Kevin B.; Aditham, Sudeep; Brontë-Stewart, Helen M. (Neurobiology of disease, 2023)
Approximately one third of recently diagnosed Parkinson's disease (PD) patients experience cognitive decline. The nucleus basalis of Meynert (NBM) degenerates early in PD and is crucial for cognitive function. The two main NBM white matter pathways include a lateral and medial trajectory. However, research is needed to determine which pathway, if any, are associated with PD-related cognitive decline. Thirty-seven PD patients with no mild cognitive impairment (MCI) were included in this study. Participants either developed MCI at 1-year follow up (PD MCI-Converters; n = 16) or did not (PD no-MCI; n = 21). Mean diffusivity (MD) and fractional anisotropy (FA) of the medial and lateral NBM tracts were extracted using probabilistic tractography. Between-group differences in MD and FA for each tract was compared using ANCOVA, controlling for age, sex, and disease duration. Control comparisons of the internal capsule MD and FA were also performed. Associations between baseline MD or FA and cognitive outcomes (working memory, psychomotor speed, delayed recall, and visuospatial function) were assessed using linear mixed models. PD MCI-Converters had significantly greater MD and lower FA (p < .001) of both NBM tracts compared to PD no-MCI. No difference was found in the MD (p = .06) or FA (p = .31) of the control region. Trends were identified between: 1) lateral tract MD and FA with working memory decline; and 2) medial tract MD and reduced psychomotor speed. Reduced integrity of the NBM tracts is evident in PD patients up to one year prior to the development of MCI. Thus, deterioration of the NBM tracts in PD may be an early marker of those at risk of cognitive decline. •Reduced integrity of cholinergic network up to 1 year prior to cognitive decline.•Cholinergic network deficits in Parkinson's disease-related cognitive impairment.•Tractography of the nucleus basalis of meynert in Parkinson's disease.